Estudio de la corrosión atmosférica en el Puerto del Mariel de Cuba. - Fernández-Soto, Dainerys; Castañeda-Valdés, Abel (Revista CENIC Ciencias Quimicas)
A study about atmospheric corrosión in the Port of Mariel of Cuba was carried out. Research related to atmospheric corrosión in Cuba, have been carried out in the coastal tropical climate without the presence of a large industrial potential as in the study zone selected. Seven exposure sites to different distance from the sea were selected, where for determination and evaluation of chloride and sulphate ions or sulfurs compounds deposition device were placed, as well as probes of different metallic materials more using in the construction industry. A sensor to measure the relative humidity temperature complex in one of the exposure site was placed during the year of study. The results showed that corrosión aggressivity levels estimations from deposition behavior of the aggressive agents and climatic parameter were corresponded with corrosión aggressivity determination from corrosión rate obtained during the year of the study in the four metallic materials tested more use in the construction industry more the galvanized steel. It demonstrated that copper, zinc and aluminum were the metallic materials most affected. The most influential factor in atmospheric corrosión in the five metallic materials was the chloride deposition under a industrial coastal atmosphere, followed by sulfur compounds deposition and the relative humidity temperature complex